Landscape network congruency at the ecoregion scale: can we expect corridor 'umbrellas'?. Issue 4 (3rd July 2016) - Perkl, Ryan M.; Baldwin, Robert F.; Trombulak, Stephen C.; Smith, Garrett R.
ABSTRACT: Conservation planners are faced with numerous choices regarding 'what to connect' when modeling landscape networks on an ecoregion scale. A simplifying assumption is often that coarse-scale corridors may provide overlapping or 'umbrella' effects for multiple conservation scenarios. To examine this, we assessed differences in connectivity models arising from four different conservation scenarios for the transboundary Northern Appalachian/Acadian Ecoregion (330, 000 km 2 ). Models resulted in networks comprised of varying levels of connectedness, suggesting the presence of local connectivity at several sub-ecoregion scales, but diminished ecoregion-scale connectivity. Our results also indicate that selecting 'what to connect' at the ecoregion scale strongly influences the location and extent of modeled corridors. Further, our evidence suggests that landscape networks derived for one scenario are not likely to produce far-reaching corridor umbrellas or highly coincident landscape networks for alternative conservation scenarios with varying goals. As a result, alternative landscape networks should not be considered functionally equivalent.